2020
DOI: 10.3171/2019.4.jns19252
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic agents and traumatic brain injury in the elderly population: hemorrhage patterns and outcomes

Abstract: OBJECTIVEAmong the elderly, use of antithrombotics (ATs), antiplatelets (APs; aspirin, clopidogrel), and/or anticoagulants (ACs; warfarin, direct oral ACs [DOACs; dabigatran, rivaroxaban, apixaban]) to prevent thromboembolic events must be carefully weighed against the risk of intracranial hemorrhage (ICH) with trauma. The goal of this study was to assess the risk of sustaining a traumatic brain injury (TBI), ICH, and poorer outcomes in relation to AT use among all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
81
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 38 publications
11
81
4
1
Order By: Relevance
“…The close association between older age and comorbidity is in line with other recent TBI studies [ 3 , 32 , 33 ]. Antithrombotics are associated with increased risk of intracranial hematoma after blunt head injury, progression of intracranial hematoma, increased morbidity, and mortality in the TBI population [ 34 37 ]. Based on observation in clinical practice, comorbidities appear to be a more important factor than age itself for treatment decisions in patients with TBI.…”
Section: Discussionmentioning
confidence: 99%
“…The close association between older age and comorbidity is in line with other recent TBI studies [ 3 , 32 , 33 ]. Antithrombotics are associated with increased risk of intracranial hematoma after blunt head injury, progression of intracranial hematoma, increased morbidity, and mortality in the TBI population [ 34 37 ]. Based on observation in clinical practice, comorbidities appear to be a more important factor than age itself for treatment decisions in patients with TBI.…”
Section: Discussionmentioning
confidence: 99%
“… 60 One study on head trauma in elderly patients (>65 years of age, n = 1365) found a lower incidence of intracranial hemorrhage with NOACs than warfarin. 61 The risk of falls may be reduced by appropriate strategies, in particular with a multidisciplinary assessment of the risk, the treatment of remediable pathologies and the prescription of preventive interventions such as exercise programs; home environmental assessment, etc. A Markov decision analytic model showed that a patient receiving VKAs would need to fall 295 times for the risk of a subdural hematoma to exceed the benefits derived from anticoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…ACs drugs like warfarin are associated with the higher increased risk for ICH in the setting of TBI[ 47 ] and with elevated chances of ICH progression in the follow-up period. [ 48 ] Conversely, DOACs have a considerably lower rate of development of ICH compared to warfarin[ 49 50 ] and lesser chances of ICH progression. [ 48 ] These data support the safer profile of DOACs than ACs, suggesting that they should be used as first choice in older patients with high risk of falling.…”
Section: Discussionmentioning
confidence: 99%